Pengembangan Perangkat Pembelajaran Team Based Learning- Pbl Berbantuan WhatsApp dan Facebook Messenger - Supartin, Supartin; Galanggadjir, Triska Laurensya; Arbie, Asri (Universitas PGRI Sumatera Barat, 2021)
The Covid 19 pandemic has a major impact on all sectors of life including in the world of education. The implementation of PJJ (Distance Learning) requires new innovations in the development of learning devices so that learning continues to run well even though learning activities are carried out at home. The development model used in this research is the 4D Development model. The result of this study is that the learning device is said to be